Handbook of research on applied data science and artificial intelligence in business and industry - Chkoniya, Valentina, 1977- (Advances in business information systems and analytics (ABISA) book series., 2021)
"This book provides an overview of the concepts, tools and techniques behind the increasing field of Data Science and Artificial Intelligence, applied to business and industries"--